“Implementación de contactores y variadores de frecuencia para el proceso de enseñanza y aprendizaje a los estudiantes de la Universidad Técnica de Cotopaxi extensión La Maná”. - Arias Mera, Manuel Isaac (2022)
For implementing a didactic module of contactors and frequency variators, the researchers evidenced the existence of problems derived from the lack of it. The direct beneficiaries of this study are the students of Electromechanical Engineering career at the Technical University of Cotopaxi in La Maná Extension, so that they can acquire practical knowledge of the processes carried out in the industry. For verifying this project's implementation, techniques, experimental methods, and a set of activities allowed to correct the defects found in the structure. This project aims to improve the teaching and learning process by detailing the procedures in the design, programming, and implementation of the control system, where the elements and aspects of the process are described. It is essential to mention that the bibliographic research type is crucial for the project development because it lets to acquire knowledge over the "development of the didactic board of contactors and frequency variators” through different bibliographic sources and field methodology usage in the block B of the University. In addition, tests must be performed on the inputs and outputs of digital and analog signals supported by a multimeter to confirm the continuity and observe the established variables on the "touch" panel. For the development of this research work, most of the information was compiled from manuals and technical magazines to know the operation of the required components, since there is not too much information on some frequency inverters as is the case of the frequency inverter SINAMICS V20, the logo 230 RCE, the soft starter ABB PSR25, among others.